Distinct neonatal hyperammonemia and liver synthesis dysfunction: case report of a severe MEGDHEL syndrome - Kirchberg, Ina; Lainka, Elke; Gangfuß, Andrea; Kuechler, Alma; Baertling, Fabian; Schlieben, Lea D.; Lenz, Dominic; Tschiedel, Eva (Frontiers in Pediatrics, 2024)
Background / Purpose MEGDHEL syndrome is a rare autosomal recessive metabolic disorder, which is characterized by 3-methylglutaconic aciduria with deafness-dystonia, hepatopathy, encephalopathy and Leigh-like syndrome. It is caused by biallelic pathogenic variants in the SERAC1 gene. Due to the unspecific symptoms and the diverse manifestations of the clinical phenotype, the diagnosis is challenging. Infantile MEGDHEL syndrome often has a severe disease course with acute liver failure. Differentiation from other metabolic disorders is difficult and requires a multidisciplinary approach.A two-day-old small for gestational age neonate was admitted to our pediatric intensive care unit (PICU) due to severe liver failure with distinct hyperammonemia and hypoglycemia without elevation of transaminases or cholestasis. Due to high ammonia level, continuous hemodialysis was established immediately after admission. In addition, protein intake was stopped, and the patient anabolized with intravenous glucose. Temporary stabilization could be achieved after four days. In the further course, severe neurological and cardiocirculatory complications occurred, which ultimately led to the infant's death. In the metabolic diagnostics, a pronounced lactate acidosis and in urine an increased excretion of 3methylglutaconic acid as well as other metabolites of mitochondrial energy metabolism has been the leading findings besides the hyperammonemia. Post-mortem trio whole genome analysis detected a homozygous pathogenic variant in SERAC1 with evidence of SERAC1 deficiency leading to the diagnosis of infantile MEGDHEL syndrome.When pediatricians are faced with hepatopathy or even acute liver failure without elevation of transaminases or cholestasis in newborns, SERAC1 deficiency should be considered as a potential differential diagnosis. The initial treatment is based on the recommended management of suspected metabolic disorders. Even while no cure is available yet, patients should be offered proper supportive management through a multidisciplinary team. In addition, genetic confirmation of the diagnosis is important for the families, especially regarding further family planning.If a newborn presents with hyperammonemia, hypoglycemia and impaired liver synthesis function without elevation of transaminases or cholestasis, the possible presence of MEGDHEL syndrome due to a SERAC1 mutation should be considered.Patient consent statement: Complete informed consent was obtained from the patient parents for the publication of this case report.